"I Was Losing That Sense of Her Being Happy"—Trans Children and Delaying Social Transition. Issue 2 (15th March 2022) - Horton, Cal
Abstract: Within transgender children's healthcare there are two competing paradigms on appropriate support for pre-pubertal trans children, 'affirmation' and 'delayed transition'. Parents of trans children accordingly face conflicting advice on the appropriate timing of 'social transition', where social transition connotes external acceptance and affirmation of a child's identity. This innovative research brings experience-based insights from 30 UK-based parents (93% female), who supported 30 trans children to socially transition at an average age of seven years old (range 3–10 years old). Data were analyzed through inductive reflexive thematic analysis to understand interviewee experiences and perceptions related to the timing of social transition. Analysis highlights two broad themes; firstly, the influence of cisnormativity on delay, with parents revealing deeply embedded resistance to trans possibilities. Secondly, parental perception of delays causing distress, even in families who may be considered affirming. The study reinforces existing research on the importance of affirmation and family support. The study also highlights the support parents may need to overcome cisnormative barriers to supportiveness, and the distress, frustration and trauma that trans children may experience, even within affirming families.